Content of exDNA in rooster’s seminal plasma as a potential biomarker of sperm viability - A. A. Kurochkin; T. I. Kuzmina; A. O. Prituzhalova (Аграрная наука Евро-Северо-Востока, 2024)
Searching biomarkers, that have an early prognostic trait and determinate functional status of male gametes Gallus Gallus is a promising direction for improving ejaculate’s quality reproductive characteristics. In context of a decreasing reproductive performance due to breeding selection of birds aimed to improving economically useful traits, this approach to selecting males, based on their sperm quality production will make it possible to evaluate sperm in a short time and identify potentially the best producers at early stages. The study determined possibility of using exDNA as a potential biomarker that determines quality indicators of native sperm obtained from roosters. Significant correlations were revealed between exDNA and proportion of cells with damaged plasma membrane (r = 0.35, p<0.05), which indicates a possible connection of this  biomarker with necrotic and apoptotic processes occurring in cells. Variation coefficient of exDNA indicator was 30.28 %, demonstrating the possibility of using the proposed biomarker (exDNA concentration in the seminal fluid of Gallus Gallus)  as a predictive criterion for assessing quality of male gametes. Significant correlations (r = 0.51, p<0.05) were established between proportion of cells exposed to oxidative stress, proportion of cells with damaged plasma membrane and high mitochondrial activity, which indicates negative impact of reactive oxygen species on the plasma membrane integrity and relationship increased generation of reactive oxygen species with functional status of mitochondria. On the basis of the analysis of research results, the indicator “exDNA content in seminal fluid” should be considered as a preventive non-invasive biomarker of the functional state of male gamete Gallus Gallus.